Carinacuma umesi, a new genus and species of bodotriid cumacean (Crustacea: Malacostraca: Peracarida) from shallow waters of the Maryland Coastal Bays, Mid-Atlantic region, USA - Morales-Núñez,Andrés G.; Chigbu,Paulinus (PeerJ, 2021)
Carinacuma, a new bodotriid cumacean genus, is diagnosed to receive Spilocuma watlingi Omholt & Heard as its type species and C. umesi sp. nov., described from shallow waters (0.8 to 2.8 m) on the Mid-Atlantic coast of North America. Carinacuma gen. nov. has its closest affinities to the North American genera Spilocuma and Mancocuma, but can be distinguished from them and the other genera within the subfamily Vaunthompsoniinae by a combination of characters, including the presence of a dorsal carina or keel on pereonite 3 of the female, morphology of the antenna, absence of pleopods in the male, and the setation and segmentation of the uropods. Carinacuma umesi sp. nov., can be differentiated from its northern Gulf of Mexico cognate, C. watlingi comb. nov. by several characters, including: (1) maxilliped 3 carpus of female with inner margin bearing four to five simple setae, (2) uropod peduncle of female with inner margin bearing one sub-distal micro-serrate seta with single sub-terminal medial setule, (3) male antennule peduncle articles 1–2 sub-equal length, and (4) male antennule accessory flagellum slightly longer than basal article of main flagellum. A key to the five known males lacking pleopods within Vaunthompsoniinae is provided.
Keywords: Cumacea; Bodotriidae; Vaunthompsoniinae; Carinacuma gen. nov.; Carinacuma umesi sp. nov.; North America; Maryland; Mid-Atlantic coast